Investment in Renewable Energy as a Tool to Increase the Economic Growth of the Arab Countries: A Comparative Standard Study between Oil and Non-Oil Producing Countries - Zerzar layachi; Medahi mouhamed (Solar Energy and Sustainable Development, 2016)
The aim of this paper is to study the dynamics of renewable energies in the Arab countries by using statistical tools through the analysis of the international move to renewable energies as an alternative to the traditional energies in the fist axis. The second part will analyze and compare the evolution of renewable energies in the Arab countries through dividing them into oil producing countries and non- oil producing ones .In the third axis, tools of econometrics are used to predict the international trend and that of the Arab countries , both oil and non-oil to renewable energy . The last part estimates the standard model about the possible impact of moving energies on economic growth rates in the Arab countries. Th study concluded that the growing renewable energies will be different in the constituent countries of the study sample, in addition to the weak impact of the move towards renewable energies on economic growth in the Arab countries.